Impact of extreme exercise at high altitude on oxidative stress in humans. (7th December 2015) - Quindry, John; Dumke, Charles; Slivka, Dustin; Ruby, Brent
Abstract : Summary of oxidative stress responses to exercise and recovery at low and high altitudes Independent of altitude oxidative stress is induced by acute exercise in proportion to either exercise intensity or exercise duration. Redox balance, as indicated by depletion of endogenous antioxidants (AO) and production of reactive oxygen species (ROS), shifts toward oxidative stress during and following exercise at low and high altitudes (hiker symbol). Recent findings suggest that recovery (reclined stick figure) from high altitude exercise or ascension from low‐to‐high altitude is marked by an attenuated oxidative stress response as compared with recovery at lower elevations. Moreover, early findings indicate that redox‐sensitive adaptations to exercise‐induced oxidative stress may be negatively impacted by high altitude recovery. In contrast to exercise, healthy rested (inset) individuals at low altitude are often in redox balance and without oxidative stress. Abstract: Exercise and oxidative stress research continues to grow as a physiological subdiscipline. The influence of high altitude on exercise and oxidative stress is among the recent topics of intense study in this area. Early findings indicate that exercise at high altitude has an independent influence on free radical generation and the resultant oxidative stress. This review provides a detailed summary of oxidative stress biochemistry as gleaned mainly from studies of humans exercising at high altitude. Understanding of the human response to exercise at altitude is largely derived from field‐based research at altitudes above 3000 m in addition to laboratory studies which employ normobaric hypoxia. The implications of oxidative stress incurred during high altitude exercise appear to be a transient increase in oxidative damage followed by redox‐sensitive adaptations in multiple tissues. These outcomes are consistent for lowland natives, high altitude acclimated sojourners and highland natives, although the latter group exhibits a more robust adaptive response. To date there is no evidence that altitude‐induced oxidative stress is deleterious to normal training or recovery scenarios. Limited evidence suggests that deleterious outcomes related to oxidative stress are limited to instances where individuals are exposed to extreme elevations for extended durations. However, confirmation of this tentative conclusion requires further investigation. More applicably, altitude‐induced hypoxia may have an independent influence on redox‐sensitive adaptive responses to exercise and exercise recovery. If correct, these findings may hold important implications for athletes, mountaineers, and soldiers working at high altitude. These points are raised within the confines of published research on the topic of oxidative stress during exercise at altitude.